A Context Aware Cooperative Communication Method in Wireless Sensor Networks. (14th June 2015) - Kim, Hyunduk; Kim, Chulki; Kim, Jaehun; Seo, Minah; Lee, Seok; Lee, Taikjin
In wireless sensor networks, the clustering methods proposed to improve the energy efficiency of a sensor network can lead to severe energy consumption by the cluster heads. Furthermore, in the case where an unbalanced cluster structure is generated, the overall lifetime of the sensor networks is significantly reduced. Moreover, existing cooperative communication methods, for example, CoopLEACH, waste energy because of the unilateral cooperative communication method, which does not consider the distance between the sink and cluster heads. To solve these problems, this paper proposes a novel method that transmits and collects data according to the density of the nodes and the distance between the sink and cluster heads. Through extensive performance studies, we observed that our method is 12% more energy-efficient than CoopLEACH.